Thermo-mechanical properties of kenaf-filled unplasticized polyvinyl chloride composites - Abd Rahman, Mohd Firdaus (2012)
Composites of kenaf filled unplasticized poly (vinyl chloride) (uPVC) were produced by a compression moulding method. The main objective of this study is to investigate the effects of kenaf filler (KF) loading, incorporation of poly [methylene poly (phenyl isocyanate)] (PMPPIC), and electron beam irradiation (EBI) treatment on mechanical and thermal properties of KF/uPVC composites. Tensile test, flexural test, impact test and thermo gravimetric analysis (TGA) were performed to determine those properties. The results showed that the use of 30% KF content in untreated KF/uPVC composite contributed to the about 12% enhancement in tensile strength. Furthermore, the incorporation of PMPPIC coupling agent in similar composition has improved the tensile and flexural strength by about 22% and 11%, respectively. Adversely, the electron beam (EB) irradiated KF/uPVC composite without PMPPIC has failed to enhance the tensile, flexural, and impact strength of pure uPVC matrix. However, the presence of PMPPIC in irradiated composite at 30% filler content has amplified the tensile and flexural strength. The TGA results showed KF degraded before uPVC. As the amount of KF content was increased from 10% to 40%, the thermal stability of KF/uPVC composite decreased. This occurs in both composites that incorporated PMPPIC and without PMPPIC. In conclusion, KF has the potential to be used as filler in uPVC composites as it enhanced the stiffness, mechanical strength and reduced the materials cost of the composites by about 26%. The KF/uPVC composite that incorporated with coupling agent appeared to have better tensile and flexural strength since PMPPIC induced better interfacial adhesion between KF and the uPVC. The EB irradiated KF/uPVC composite without PMPPIC has failed to improve the mechanical properties which is suggested due to the structural distortion and random chain scission (degradation) of uPVC main chain. However, the irradiated composite that incorporated PMPPIC has demonstrated better mechanical properties and this might be due to cross-linking reaction or interaction of free radicals produced in the irradiated uPVC and KF that enhanced the KF-uPVC matrix adhesion.